2016
DOI: 10.1111/jvs.12375
|View full text |Cite
|
Sign up to set email alerts
|

Seed germination traits can contribute better to plant community ecology

Abstract: Analyses of functional traits have become fundamental tools for understanding patterns and processes in plant community ecology. In this context, regenerative seed traits play an important, yet overlooked, role because they largely determine the ability of plants to disperse and re-establish. A survey of recent publications in community ecology suggests that seed germination traits in particular are neglected at the expense of other relevant but overused traits based only on seed morphology. As a response to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
204
1
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(222 citation statements)
references
References 65 publications
(146 reference statements)
7
204
1
10
Order By: Relevance
“…This contrasts with findings that show adaptations of seeds and seedlings determining range limits, community assembly, and population dynamics (Morin et al, 2007;Poorter, 2007;Donohue et al, 2010;Huang et al, 2016;Jiménez-Alfaro et al, 2016). Harper et al (1965) and Grubb (1977) demonstrated how important 'regeneration niches' and 'safe sites' are by showing that biotic and abiotic environments of plants during germination, establishment of seedlings and onward growth determine position and success of adults.…”
Section: Introductionmentioning
confidence: 76%
“…This contrasts with findings that show adaptations of seeds and seedlings determining range limits, community assembly, and population dynamics (Morin et al, 2007;Poorter, 2007;Donohue et al, 2010;Huang et al, 2016;Jiménez-Alfaro et al, 2016). Harper et al (1965) and Grubb (1977) demonstrated how important 'regeneration niches' and 'safe sites' are by showing that biotic and abiotic environments of plants during germination, establishment of seedlings and onward growth determine position and success of adults.…”
Section: Introductionmentioning
confidence: 76%
“…Germination is a particularly vulnerable stage in the plant life cycle, representing the transition from the seed to an actively-growing seedling. Supporting this transition is key to the successful establishment of newly introduced native species, and disrupting this transition could provide a means to reduce the abundance of invasive species (Jimenez-Alfaro et al 2016). Invasive species are able to outcompete or displace native species, and the timing of germination, along with the overall proportion of seeds that germinate (hereafter percent germination) seem to play an important role in their success (Guthrie et al 2016;Vaughn and Young 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly, an ecologically-guided approach is resolving dormancy and germination characteristics, particularly by considering the biotic and abiotic factors influencing regeneration and seedling establishment in the field. Regeneration traits of species can be used to inform and better understand the patterns and processes in plant community ecology for restoration and threatened species conservation (Jiménez-Alfaro et al 2016;Merino-Martín et al 2017). Such seed (and plant) trait data have yielded many discoveries on the ecology and evolution of Australian plants (Moles 2018) and ongoing work to understand the influence of such morphological and physiological traits with key life history stages such as dispersal (e.g.…”
Section: Emerging Themes and Future Directionsmentioning
confidence: 99%